The Influence of Leadership Style and Incentive Provision on Employee Work Motivation at Peak Everest Mining LDA, Timor-Leste - Carvalho Soares, Sebastiao Barreto de; Lestari, Ayu Mey; Kosasih, Kosasih; Yuliaty, Farida (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the influence of leadership style and incentivization on employee work motivation at Peak Everest Mining LDA, a mining company operating in Timor Leste. The background of this research is based on the importance of effective leadership roles and fair incentive systems in shaping the performance of motivated human resources, especially in the mining industry which demands high productivity and job security. The research method used is quantitative with a survey approach. Data was collected through a questionnaire that was distributed to 110 respondents out of a total population of 150 employees. The data analysis technique used was multiple linear regression, with classical assumption tests that included normality, multicollinearity, and heteroscedasticity tests. The results of the study show that leadership style and incentivization have a positive and significant effect on work motivation both partially and simultaneously. Leadership style has a regression coefficient of 0.998 with a significance value of 0.0000, while incentives have a regression coefficient of 2.056 with a significance of 0.0000. The F test showed that the two variables together had a significant effect on work motivation with an F-value of 733.863 and a p-value of 0.0000. A determination coefficient (R²) of 0.932 indicates that 93.2% variation in work motivation can be explained by leadership style and incentivization. This study provides the implication that improving the quality of leadership and providing effective incentives are indispensable in building optimal work motivation in the Timor Leste mining work environment.